Tuning the magnetic properties of multiferroic BiFeO3 : From bulk to nanoscale. (2022)
This multiferroic materials exhibit simultaneously magnetic and ferroelectric ordering. The archetypical multiferroic material, BiFeO3 (BFO), is a unique material with both properties present at room temperature. The BFO has attracted much attention due to its high ferroelectric Curie temperature (1103K) and high antiferromagnetic Neel temperature (643K) in bulk form. The antiferromagnetic ordering instead of a ferromagnetic one has limited the technological applica tions exploiting the ferroic order with both, voltages, and magnetic fields. In this thesis, we explore new routes of magnetic control via nano-structuration in the form of nanoparticles (NPs). The confinement at the nanoscale allows tuning the antisymmetric anisotropy (also called Dzyaloshinskii-Moriya interaction) that causes a distortion of the antiferromagnetic-coupled Fe spins along the [111]h direction and giving rise to a spin cycloid (Lambda). Therefore, NPs with sizes close to the (Lambda). may exhibit interesting magnetic phenomena. We fabricated the BFO NPs by the sol-gel method . We tune the nanoparticle size by varying the calcination temperature which allowed us to go from a few nm up to values close to bulk. All fab ricated BFO NPs show an R3c rhombohedral structure with a residual strain that is a function of the NP size. We found that the magnetic ordering of the BFO NPs is strongly affected by the structural disorder which inevitably arises when the nanoparticle size is decreased to a nanometer scale. Using HRTEM images, we identified that the planes at the surface are better defined in relation to those that are at the core of the particle, we can think that the degree of structural ordering between the surface and core is different due to presence of strain . We found a mixture of different magnetic contributions from superparamagnetism up to weak-ferromagnetis . Furthermore, the complex magnetic structure of the the NPs gives rise to different magnetic transitions at low temperature and high temperature . These transitions are fingerprints of a disorder-driven magnetism present in our BFO NPs. This is confirmed by models based on an atomic vibration instability approach. As a result, a magnetic glassy state can be identified in the smallest particles together with a magnetic core-shell structure in the bigger ones. We employed several characterization techniques to deconvolute the magnetic contributions as a function of size and strain, from in-house magnetometry measurements up to synchrotron-based X-ray magnetic dichroism measurements. In addition to the magnetic measurements, we investigated the optical properties of BFO using Ra man and UV-vis spectroscopy. The results showed a high coincidence between peaks as a consequence of the high crystallinity of our nanoparticles. Using the UV-vis spectroscopy measurements, the bandgap can be deduced by the well-established Tauc plot method. We find that the optical band gap is reduced with decreasing nanoparticle size. These results point to a novel route to control the optical properties in addition to the multiferroic properties of BFO NPs. We employed Density Functional Theory with input from the experimental crystal structures to link the crystallographic and strain contributions to observed magnetic moment . Interestingly, we find that due to the strong phonon-magnon coupling the strain effects alone can be responsible for the observed magnetic tunning. As a result of this thesis, we identify great opportunities for BFO NPs for spintronic applications